Policy and Practice of Participatory Extension in Indonesia:A Case Study of Extension Agents in East Java Province - Edi Dwi Cahyono; Robert Agunga (Journal of International Agricultural and Extension Education, 2016)
Participatory extension approach, also called demand-driven or pluralistic extension approach is gaining widespread popularity as a democratic process of getting smallholder farmers involved in decision-making. The approach was heavily promoted in Indonesia as a law enacted in 2006. This study, conducted in 2013, almost eight years after its introduction, was carried out to determine how effective the policy was being implemented. A survey of 159 extension agents in 33 sub-regencies of Malang Regency in East Java Province in Indonesia revealed that while extension workers were familiar with the participatory extension policy and were actually practicing it they felt that it was not successful. They also felt that they the communication skills to implement it. Lastly, they felt that while social media can enhance extension communication with farmers, they needed training in the use of Information and Communication Technologies (ICTs) in extension. Our recommendation was that training extension workers in communication and development was critical to helping them undertake the complex process of implementing the participatory extension approach while at the same time facilitating integrated rural development
Keywords: participatory extension; project implementation; extension effectiveness; integrated rural development; extension in Indonesia